2021
DOI: 10.3389/fcvm.2021.647785
|View full text |Cite
|
Sign up to set email alerts
|

Post-ischemic Myocardial Inflammatory Response: A Complex and Dynamic Process Susceptible to Immunomodulatory Therapies

Abstract: Following acute occlusion of a coronary artery causing myocardial ischemia and implementing first-line treatment involving rapid reperfusion, a dynamic and balanced inflammatory response is initiated to repair and remove damaged cells. Paradoxically, restoration of myocardial blood flow exacerbates cell damage as a result of myocardial ischemia–reperfusion (MI-R) injury, which eventually provokes accelerated apoptosis. In the end, the infarct size still corresponds to the subsequent risk of developing heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 258 publications
(282 reference statements)
0
36
0
Order By: Relevance
“…Though not direct evidence for ILCs in MIRI, several groups (22,(41)(42)(43) have reported roles for ILCs in IRI and ILC-related cytokines in MIRI, suggesting that ILCs can play important roles in MIRI, with ILC2s being the most promising candidate.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though not direct evidence for ILCs in MIRI, several groups (22,(41)(42)(43) have reported roles for ILCs in IRI and ILC-related cytokines in MIRI, suggesting that ILCs can play important roles in MIRI, with ILC2s being the most promising candidate.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…24-72 hours after MIRI, expression of pro-inflammatory cytokines decreased significantly, and levels of fibrotic mediators such as TGF-b and IL-10 showed a continuous and rapid increase, reflecting suppression of acute inflammation and transition to cardiac repair and proliferation (41,42). Recently, Pluijmert et al (43) summarized the multifactorial and dynamic process of the inflammatory response in MIRI, including TNF-a, IL-4, IL-13, IL-10 and TGF-b. These results suggested that cytokines, especially those related to ILCs, play important roles in MIRI (22).…”
Section: The Role Of Ilcs In Myocardial Ischemia-reperfusion Injurymentioning
confidence: 99%
“…MIF playing an essential role in ischemic preconditioning-induced myocardial protection may ameliorate altered cardiac function and adverse cardiac remodeling through various ways, including suppression of ischemia-induced salvage kinase pathway, CD74/ AMP-activated protein kinase signal system, and its components [47,48]. In addition, MIF exerts protective effects by suppression of myocardial healing and maintenance of cardiac function through promoting CXCR2 in resident cells [49]. Eventually, MIF can down-regulate the level of apoptosis of injured cardiac myocytes and circulating mature and progenitor endothelial cells, thereby preventing them from revascularization damage [49].…”
Section: Mif As Predictor For No-reflow Condition: Receive Operation Curve Analysismentioning
confidence: 99%
“…In addition, MIF exerts protective effects by suppression of myocardial healing and maintenance of cardiac function through promoting CXCR2 in resident cells [49]. Eventually, MIF can down-regulate the level of apoptosis of injured cardiac myocytes and circulating mature and progenitor endothelial cells, thereby preventing them from revascularization damage [49]. However, these data allow us to explain the plausible molecular mechanisms by which pre-PCI MIF influenced coronary blood flow recovery and myocardial function maintenance.…”
Section: Mif As Predictor For No-reflow Condition: Receive Operation Curve Analysismentioning
confidence: 99%
“…The common causative mechanism of IHD is the accumulation of emboli-commonly atherosclerotic plaques-in the coronary arteries [3], which restricts blood vessel diameters [4]. Resultantly, the blood oxygenation and blood supply to target organs are significantly reduced, affecting downstream biological processes and metabolic balance [3][4][5]. Clinical symptoms of IHD include shortness of breath; constrictions of the chest, neck, and jaw area; and cold sensations, which are further exacerbated by physical and emotional stress [2,6].…”
Section: Introductionmentioning
confidence: 99%